Impactos da dinâmica atmosférica na flutuação de potência em usinas fotovoltaicas - Daniel dos Santos Ferreira Soares (2014)
Solar energy is today the third largest renewable energy source behind the hydro and wind power. With the drop of prices of the generation assets, standalone applications (grid-off) are giving rise to large range of sized residential kilowatts to hundreds of megawatts of plants connected to grid systems. It is a worldwide phenomenon with wide integration in Europe, North America, China and Japan. On this context , Brazil have also started to build their own gridconnected photovoltaic plants across the country, giving rise to several questions on the supply capacity of these plants regarding the intermittency of its source, the solar radiation . Emerge questions about the robustness of the energy grid as the penetration of an intermittent source of energy with solar percentage rises. How consumer loads are likely to be impacted by fluctuations in supply caused by atmospheric intermittency on solar plants? The power utilities to be responsible for the quality of energy available in the grid and they must to answer this questions. In this context, Cemig is building the largest solar plant in Latin America in Sete Lagoas City - Minas Gerais to meet the demand of town and still generate knowledge about this energy source. This work, motivated by this CEMIG's project and investigates through experimental demonstration and proposal of computational models, how dynamic clouds affects the solar irradiance on the photovoltaic plants and how these plants work during these intermittencies with oscillations of shading and temperature above hundreds or thousands of interconnected modules. This work investigate the impacts of both point of view, the energetic quantity, in other words, real and local generation capacity, and power quality, in other words, the variations and voltage fluctuations produced by the photovoltaic generators connected to the distribution grid under shading conditions. The methodology was to create an electrical model of a photovoltaic array from one simple cell to an entire string, a model that simulates clouds shadows movement, a model of clear sky for comparison with measured values, a model of the electrical system independent of the model plant for versatility. In addition, the real photovoltaic modules and atmospheric data have been measured. The results show the impact of clouds on the annual average losses reaches around fifty percent of the irradiance (kW/m²) available at ground level. In relation to power quality, the impacts are shown in the power range and voltage for different levels of robustness of the power grid and changes in the direction of clouds movement over the plant. The phenomenon of voltage fluctuation is also investigated and this experiments realized, the risk of generating flicker intermittence by clouds was removed.